Development and relationship between the judgment of the speed of passage of time and the judgment of duration in children - Martinelli, Natalia N.; Droit-Volet, Sylvie (Frontiers in Psychology, 2023)
This study examined the relationships between the awareness of the speed of the passage of time, the judgment of durations and experiential factors in children aged 4 - 9 years. They were asked to judge the duration and the speed of the passage of time for different intervals (second and minutes), and to rate their feelings (arousal, happiness, sadness, task difficulty) during each interval. The results indicated that 8-9-year-olds’ judgment of the passage of time is extremely flexible and context-dependent, representing the duration and/or the individual changes in subjective experience (emotion). In contrast, young children’s judgment of the passage of time was not related to duration. However, their judgments were not given randomly. They judged that time passed more quickly when they felt happier and more alert. The passage-of-time judgment was therefore initially grounded in emotional and sensory-motor experience, i.e., in their perception of changes (acceleration and deceleration) in self-movement (successions of states and their extension). Therefore, duration judgment and passage-of-time judgment initially develop separately and are later combined when children understand the logical link between speed and duration.